Dipeptidyl Peptidase-4 Inhibitor-Associated Bullous Pemphigoid - Tasanen, Kaisa; Varpuluoma, Outi; Nishie, Wataru (Frontiers in Immunology, 2019)
Bullous pemphigoid (BP) is an organ-specific autoantibody-mediated blistering skin disease that mainly affects the elderly. Typical clinical features include the widespread blisters, often preceded by and/or associated with itchy urticarial or eczema-like lesions. BP patients have circulating autoantibodies against BP180 and/or the plakin family protein BP230 both of which are components of hemidesmosomes in basal keratinocytes. Most BP autoantibodies particularly target the epitopes within the non-collagenous NC16A domain of BP180. Clinical findings and murine models of BP have provided evidence of a pathogenic role of anti-NC16A autoantibodies. However, it is largely unknown what triggers the breakage of immunotolerance against BP180 in elderly individuals. The incidence of BP has been increased over the past two decades in several countries. Aside from aging populations, the factors behind this phenomenon are still not fully understood. Neurodegenerative diseases such as multiple sclerosis, Parkinson’s disease, and certain dementias are independent risk factors for BP. Recently several case reports have described BP in patients with diabetes mellitus (DM) patients who have been treated with dipeptidyl peptidase-4 inhibitors (DPP-4i or gliptins), which are a widely used class of anti-DM drugs. The association between the use of DPP-4is, particularly vildagliptin, and BP risk has been confirmed by several epidemiological studies. Evidence suggests that cases of gliptin-associated BP in Japan display certain features that set them apart from cases of ‘regular’ BP. These include a “non-inflammatory” phenotype, targeting by antibodies of different immunodominant BP180 epitopes, and a specific association with the human leukocyte antigen (HLA) types. However, recent studies in European populations have found no major differences between the clinical and immunological characteristics of gliptin-associated BP and ‘regular’ BP. The DPP-4 protein (also known as CD26) is ubiquitously expressed and has multiple functions in various cell types. The different effects of the inhibition of DPP-4/CD26 activity include, for example, tissue modeling and regulation of inflammatory cells such as T lymphocytes. Although the pathomechanism of gliptin-associated BP is currently largely unknown, investigation of the unique effect of gliptins in the induction of BP may provide a novel route to better understanding of how immunotolerance against BP180 breaks down in BP.